Kinetics and Mechanism of the Reaction of Gold(III) Chloride Complexes with Formic Acid - Paclawski, Krzysztof (Journal of Mining and Metallurgy, Section B: Metallurgy, 2015)
In this work, the result of kinetic studies of the redox reaction of gold(III) chloride complexes ([AuCl4]-) with formic acid, are presented. Obtained data suggest the complex character of the reaction which leads to the [AuCl2]- and [AuCl3(COOH)]- ions formation as intermediates. In the pH range over 2.5 the final product of the reaction is metallic gold. From the analysis of kinetic data, the rate limiting step is found to be the gold metallic phase formation. The stage of Au(III) reduction is relatively fast with the second-order rate constant equal to 61.8 M-1s-1 at temperature 50 oC. The rate of the studied reaction depends on the temperature, reactants concentration and chloride ions concentration. As a result of the data analysis, the scheme of the reaction path has been suggested. Also, the values of enthalpy and entropy of activation for the reaction have been determined.